Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1055/s-0037-1606354
|View full text |Cite
|
Sign up to set email alerts
|

Deep Brain Stimulation in Patients with Parkinson's Disease: Effect on Psychiatric Symptoms and Quality of Life

Abstract: DBS of the STN in patients with PD is associated with an improvement in psychiatric (affective and sleep-wake cycle) symptoms, clinical motor symptoms, and quality of life at 1 year after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…Varied outcomes across PDQ-39 domains may be influenced by patient's age, disease duration and severity, co-morbidities, levodopa dose and pre-operative responsiveness, genetic predisposition and non-motor symptoms [18][19][20]. Vats et al concluded that age and QoL outcomes are not significantly related which was contradicted by Dafsari et al [17,21].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Varied outcomes across PDQ-39 domains may be influenced by patient's age, disease duration and severity, co-morbidities, levodopa dose and pre-operative responsiveness, genetic predisposition and non-motor symptoms [18][19][20]. Vats et al concluded that age and QoL outcomes are not significantly related which was contradicted by Dafsari et al [17,21].…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, all PD patients fell within this age group and showed significant improvement in all domains except emotional well-being and social support. Interestingly, current research on dystonia suggests that younger age at time of surgery is correlated with better motor symptoms, but not with functionality and QoL [18]. The EARLYTISM trial challenged the concept that disease severity should be disabling and refractory to medications before surgical interventions, suggesting early DBS in mild PD [3].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations